Features of the tactical training of gymnasts performing in group exercises - Olga Kozhanova; Natalia Gavrilova; Evgeniya Tsуkozа (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to analyze the experience of trainers regarding the features of the use of tactical techniques in the construction of modern compositions of group exercises in rhythmic gymnastics. Materials & Methods: 41 rhythmic gymnastics trainers with a working experience of 1 to 40 years participated in the questionnaire, among whom were 3 honored trainers of rhythmic gymnastics in Ukraine. The trainers were asked to fill out a questionnaire, the questions of which concerned the problems of tactical training in rhythmic gymnastics. Methods used: analysis of scientific and methodological literature, questionnaires, methods of mathematical and statistical processing of the obtained data. Results: 74% of trainers do not have enough information about tactical training. Only their own observations and the experience of leading trainers are used to choose tactical behavior with gymnasts in the preparation of group exercises 60% of respondents. Conclusions: modern scientific literature does not contain enough information and practical recommendations on the development of tactical thinking and the improvement of tactical training of gymnasts in group exercises of rhythmic gymnastics. Questionnaire results showed that at the present stage of development of rhythmic gymnastics, tactical training is not given due attention, since 55% of trainers do not apply operational control over the effectiveness and speed of tactical decisions of gymnasts, do not take into account the advantages of gymnasts when choosing musical accompaniment, costumes and elements of composition, during training gymnasts to the complex elements of technology prefer only the method of multiple repetition.